2013
DOI: 10.1002/jcu.22048
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of an occult biliary‐arterial fistula using percutaneous contrast‐enhanced ultrasound cholangiography in a transplanted liver

Abstract: We present a case of a biliary-arterial communication as a consequence of the placement of an internal-external biliary drainage catheter in a liver transplant patient diagnosed on contrast-enhanced ultrasound using a novel application by injecting microbubble contrast into the catheter tube. We postulate that this method may be sensitive in identifying occult communications between the biliary tree and the vascular compartment when a catheter drain is positioned, and there is hemobilia or unexplained sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 14 publications
0
14
0
1
Order By: Relevance
“…CEUS-guided percutaneous cholangiography can delineate the biliary tree via drainage catheters, T-tubes placed intraoperatively, or during endoscopic access [206][207][208][209][210][211][212][213][214][215][216]. Intraoperatively, 3D-intracavitary CEUS can aid the surgeon to plan resection lines [206][207][208][209][210][211][212][213][214][215][216].…”
Section: Ceus Guided Biliary Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…CEUS-guided percutaneous cholangiography can delineate the biliary tree via drainage catheters, T-tubes placed intraoperatively, or during endoscopic access [206][207][208][209][210][211][212][213][214][215][216]. Intraoperatively, 3D-intracavitary CEUS can aid the surgeon to plan resection lines [206][207][208][209][210][211][212][213][214][215][216].…”
Section: Ceus Guided Biliary Interventionsmentioning
confidence: 99%
“…Intracavitary CEUS of the biliary tree is used ▪ during the intervention procedure to demonstrate puncture or cannulation success to evaluate for communication with other structures, e. g. intestine [214], pleural cavity [206,207], gall bladder, vessels [210], abscesses or others to evaluate the level of obstruction [216] ▪ after the interventional procedure to evaluate for dislodgement or occlusion.…”
Section: Ceus Guided Biliary Interventionsmentioning
confidence: 99%
“…Importantly, it can also effectively provide information on possible communication of the collection with the surrounding structures. This technique has been shown to be successful when applied to biliary drains, where it can display the biliary tree in a precise way, determine the level of obstruction, and show complications such as fistulas to vascular structures …”
Section: Discussionmentioning
confidence: 99%
“…10 ). It has also been reported that CEUS cholangiography can reveal complications associated with the percutaneous trans-hepatic biliary drainage, such as an arterial communication with a percutaneous biliary drainage tube [ 45 ], due to its superior temporal and spatial resolution. Furthermore, evaluation of post-surgical complications such as a bile leakage can be performed with CEUS (Fig.…”
Section: Biliary Interventionmentioning
confidence: 99%